THE ROLE OF THE FAMILY IN SUPPORTING THE CURE PROCESS OF PULMONARY TB PATIENTS AT THE PAMATANG RAYA HEALTH CENTER SIMALUNGUN DISTRICT - Muharti Sanjaya; Dilla Sastia Mara (PT. Radja Intercontinental Publishing, 2022)
This study entitled